2010
DOI: 10.1177/159101991001600311
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in Acute Stroke with Different Intra-Arterial Infusion Rate of Urokinase on Thrombolysis

Abstract: Intra-arterial infusion of urokinase (UK) has been widely used. However, the optimal infusion rate of the reagent has never been determined. This was investigated in the acute stage of middle cerebral artery (MCA) embolism in the present study. Sprague Dawley male rats (n=43) were randomly divided into sham-operation and five ischemic groups with urokinase administration at different infusion rates or without urokinase administration. Ischemia was induced with MCA embolism. Two hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Treatment with conventional-dose intravenous rt-PA and its combination with intraarterial urokinase were safe and feasible in patients. This strategy achieved high rates of complete arterial recanalization and good functional outcomes [32]. The administration of urokinase within 24 h after onset of stroke significantly improved the clinical outcomes as compared with a control group, which agreed with results from previous reports on the action of thrombolytic agents.…”
Section: Therapeutic Management Of Strokesupporting
confidence: 81%
“…Treatment with conventional-dose intravenous rt-PA and its combination with intraarterial urokinase were safe and feasible in patients. This strategy achieved high rates of complete arterial recanalization and good functional outcomes [32]. The administration of urokinase within 24 h after onset of stroke significantly improved the clinical outcomes as compared with a control group, which agreed with results from previous reports on the action of thrombolytic agents.…”
Section: Therapeutic Management Of Strokesupporting
confidence: 81%
“…Our previous study showed that intra-arterial administration of UK at a dose of 170 000 IU/kg (infusion at 4000 IU/min) induced neuroprotection in the rat MCAO stroke model. 10 In the present study, we observed that a neuroprotective dose of ethanol (1.5 g/kg) did not promote hemorrhage with or without thrombolytic therapy in the rat.…”
Section: Discussionsupporting
confidence: 50%
“…Neurological deficits were assessed before surgery and 0.5h, 24h, 48h, and 72h after brain reperfusion by an investigator blinded to experimental groups. Longa scoring system [ 18 ] (0 = no deficit, 1 = failure to extend left forepaw, 2 = circling to the left, 3 = falling to the left, 4 = failure to walk spontaneously and loss of consciousness, 5 = death) was used.…”
Section: Methodsmentioning
confidence: 99%